Design of information system architecture using TOGAF Architecture Development Method at Rumah Sakit Haji Jakarta - Prasetyo, Adit; Waspodo, Bayu (Universitas Trunojoyo Madura, 2025)
The Information and Technology (IT) Subdivision of Rumah Sakit Haji Jakarta plays a crucial role in supporting operations but faces serious constraints due to the dominance of manual service processes. Reliance on unstructured recording methods and non-integrated systems leads to various inefficiencies, such as hindered issue tracking, the risk of data loss, and slow service responses that impact the productivity of other units. This research aims to address these problems by producing an applicable enterprise architecture blueprint. Using a qualitative case study approach, this research applies The Open Group Architecture Framework (TOGAF) Architecture Development Method (ADM) up to the Information Systems Architecture phase. Data collection was conducted through in-depth interviews with key stakeholders, process observation, and internal document studies to obtain a comprehensive understanding. The result of this research is a structured enterprise architecture design, encompassing business, data, and application architectures. The primary artifacts produced include as-is and to-be business process models, gap analysis, and a functional design for an integrated information system consisting of a helpdesk module, inventory management, digital maintenance, and IT performance reporting. As a result, this validated blueprint provides a clear strategic guide for the hospital to implement appropriate technology solutions. The implementation of this architecture has significant potential to realize more effective, measurable, and transparent IT service management, which ultimately supports the hospital’s overall digital transformation agenda.Keywords: Enterprise Architecture, TOGAF ADM, Rumah Sakit Haji Jakarta, Helpdesk Information System, Information Systems Architecture.